Executive Committee Minutes 2021-01-28 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 12/3/2020 Approved. Chair Report. President Report. From EPC: Proposal for the Environmental Science, Geography and Management BS, as well as the Geography and Planning BA programs (and all associated course proposals and discontinuances) – Approved for Senate consent calendar. Upcoming WASC visit – approved report to Senate. From EPC: Proposal for elevation to full degree of the MA in Educational Leadership and associated discontinuance of the MA in Education with Concentration in Educational Leadership – approved for Senate consent calendar. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Discussion of Emeritus Dinner – approved to postpone until "safe." Vice President for Student Affairs Report. APARC Report. FSAC Report. CFA Report. Senate agenda approved. Good of the Order.